Effects of magnesium hydroxide on the properties of starch/plant fiber composites with foam structure. Issue 30 (3rd June 2019) - Cui, Jin-Feng; Li, Fang-Yi; Li, Jian-Yong; Li, Jian-Feng; Zhang, Chuan-Wei; Chen, Shuai; Sun, Xu
Abstract : The process and the property of starch-based composite. Abstract : In this study, magnesium hydroxide (MH) flame-retarded starch/plant fiber composites containing various MH contents (0%, 5%, 15%, 15%) were prepared and named as TF-MH0, TF-MH5, TF-MH10, TF-MH15. Thermal degradation, flame retardancy, mechanical and microscopic characteristics were discussed. The reduction in the maximum thermal degradation rate revealed that the addition of MH provided improvement in the thermal stability of the composite. The horizontal burning test and the limiting oxygen index analysis suggested enhancement in flame retardancy with increasing MH content. Moreover, the density of composites initially decreased and then increased as the MH content increased. The tensile strength was positively correlated with the density, whereas the cushioning performance was negatively correlated with the density. Microscopic analysis showed that there was an interfacial interaction between MH and thermoplastic starch, which not only improves the thermal stability, but also promotes bubble nucleation as a nucleating agent. The cells of TF-MH10 were uniform and dense, thus TF-MH10 had the best buffering performance. Furthermore, the cell structure of TF-MH15 was short in diameter, small in number, and large in skeleton thickness; therefore, TF-MH15 had the highest tensile strength.